Hospital admissions for respiratory system diseases in adults with intellectual disabilities in Southeast London: a register-based cohort study. Issue 3 (29th March 2017) - Chang, Chin-Kuo; Chen, Chih-Yin; Broadbent, Mathew; Stewart, Robert; O'Hara, Jean
Abstract : Background: Intellectual disability (ID) carries a high impact on need for care, health status and premature mortality. Respiratory system diseases contribute a major part of mortality among people with ID, but remain underinvestigated as consequent morbidities. Methods: Anonymised electronic mental health records from the South London and Maudsley Trust (SLaM) were linked to national acute medical care data. Using retrospective cohort and matched case–control study designs, adults with ID receiving SLaM care between 1 January 2008 and 31 March 2013 were identified and compared with local catchment residents for respiratory system disease admissions. Standardised admission ratios (SARs) were first calculated, followed by a comparison of duration of hospitalisation with respiratory system disease between people with ID and age-matched and gender-matched random counterparts modelled using linear regression. Finally, the risk of readmission for respiratory system disease was analysed using the Cox models. Results: For the 3138 adults with ID identified in SLaM, the SAR for respiratory system disease admissions was 4.02 (95% CI 3.79 to 4.26). Compared with adults without ID, duration of hospitalisation was significantly longer by 2.34 days (95% CI 0.03 to 4.64) and respiratory system disease readmission was significantly elevated (HR=1.35; 95% CI 1.17 to 1.56) after confounding adjustment. Conclusions: Respiratory system disease admissions in adults with ID are more frequent, of longer duration and have a higher likelihood of recurring. Development and evaluation of potential interventions to the preventable causes of respiratory diseases should be prioritised.